No Pregnancy, No Marriage: Unveiling the Ideology Behind the Discourse of ‘Sing Beling Sing Nganten’ in Balinese Marriage Culture - Luh Gede Sukardiasih; I Nyoman Weda Kusuma; Evalina Franciska Hutasoit (Universitas Udayana, 2025)
In Bali “sing beling sing nganten” phenomenon literally meaning where a couple gets married only after the bride is pregnant, often to prove her fertility, continues to shape community views on marriage and gender. Although the research was conducted in Tabanan Regency, the phenomenon is largely similar and occurs throughout Bali; therefore, the choice of location does not produce substantive differences in the findings. This study explores the ideologies embedded in “sing beling sing nganten